(untitled) (Global Journal of Science Frontier Research, 2021)
The purpose of the experiment was to determine long-term fertilization and the effects of weather on the soil properties and spring barley yields. A long-term field experiment-with crop rotations of potatoes (hemp oil from 2017), spring barley, spring barley with red clover (undersown), and red clover was established in 1960 Kuusiku, Estonia. Different barley varieties was used over the experimental period. With except the spring barley variety ’Anni’, which was tested from 1995-2019.The experiment has three fertilizer treatments: the moderate dose of fertilization (NPK1),double NPK1 (NPK2), and moderate fertilization with farmyard manure (NPK1 + FYM). After harvest, the soil samples were collected from 0-0.2 m of topsoil and 0.2-0.4 m of subsoil from each plot, using a soil drill.